KAJIAN IKONOGRAFI IKONOLOGI : “HELLO ANDY, THIS IS INDIE” (2008) DALAM SEJARAH SENI KONTEMPORER INDONESIA - Pungky Febi Arifianto; Miftahul Adi Suminto (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2023)
This study analyzes paintings by Yogyakarta artists named Indieguerillas. They have an artist duo fronted by Miko Bawono and Santi Ariestyowanti. Their painting entitled “Hello Andi, This is Indie”  will be dissected using art history as an approach to Erwin Panofsky's main theories, namely iconography and iconology. Qualitative historical research methods include searching for data through literature studies, both books and exhibition catalogues. The results of this study contain a description of the use of wayang elements with Punakawan figures in Indieguerillas' works. This is a self-reflection of satire and self-assimilation of western and eastern cultural values that exist within them. On the other hand, it provides an understanding of the spirit of the era at that time in the process of its creation so as to produce history at this time. The analysis carried out has three stages, namely pre-iconographic iconography and iconology. Through this analysis, it is found that the psychological experience and social background of the people that shape culture so that it can be considered that the work of Indieguerillas artists is a crystallization of symbols regarding the existence of artistic developments that represent human life in their time.